Reactivity controlled compression ignition engine: a review - Zuhairizan Yusof; Siti Umairah Mohamed Radzwan; Zuzailie Rosli; Aldaedin Alaa Razzaq Abdulmohsin; Mohd Radzi Abu Mansor (Penerbit Universiti Kebangsaan Malaysia, 2019)
Reactivity Controlled Compression Ignition (RCCI) is an efficient dual-fuel engine combustion technology that can offer low emission level in internal combustion engine technology. RCCI technology works by generating reactivity stratification in the cylinder with two fuels of different cetane numbers. To accomplish reactivity stratification, the fuel with lower reactivity is premixed with air before charging into the combustion chamber. The fuel with higher reactivity is injected subsequently using a direct injector. By properly manipulating the fuel ratio and the injection timing, one is able to regulate the combustion phasing and lessen the rates of pressure rise and heat release thanks to the reactivity gradient. Meanwhile, factors such as compression ratio (CR) and piston bowl geometry could influence the characteristics of RCCI. Evaporation, mixing, and combustion processes are dependent on the fuel type. In this paper, recent progress to improve the combustion processes with several aspects of changing of RCCI engine parameter are reviewed, such as management strategy, compression ratio, EGR rate, and bowl geometry.